A Banki–Michell turbine for in-line water supply systems. Issue 5 (3rd September 2017) - Sammartano, Vincenzo; Sinagra, Marco; Filianoti, Pasquale; Tucciarelli, Tullio
ABSTRACT: The design of a novel Banki–Michell type turbine, to be located in existing water pipelines, is proposed. The turbine has a very efficient diffuser which allows the turbine to be compact and, most importantly, to have in-line flanges for minimal piping modifications at existing sites. This turbine combines a simple geometry with stable efficiency in a wide range of water discharges. The design procedure estimates the outer diameter of the impeller, its width and the geometry of the diffuser. A series of experimental tests has been carried out to measure the efficiency of the proposed turbine prototype. The turbine was tested in two different configurations, with and without rotational velocity regulation. The results of the tests showed that rotational velocity adaptation improves turbine efficiency in a wide range of flow rates. A significant reduction of the optimal velocity ratio, with respect to the predicted values, is likely due to 3D effects not accounted for in the design procedure. A simple way to roughly estimate this extra energy dissipation is derived from experimental data.